Application of four molecular markers for breeding peach aphid (Myzus persicae Sülzer) resistance - CHEN Xuejia; LIU Mingjie; WU Jinlong; WANG Xinwei; CHEN Changwen; LI Yong; WANG Lirong (Guoshu xuebao, 2025)
[Objective] Phenotypic evaluation of green peach aphid (Myzus persicae Sülzer) infestation was conducted during the peak occurrence period in spring. The developed molecular markers for aphid resistance were validated on a large scale within the population. Highly accurate molecular markers were employed to screen out aphid-resistant peach individuals, followed by genotyping to identify their resistance-associated alleles. This study provides valuable support for selecting aphid-resistant parental lines in peach breeding programs. [Methods] Using hybrid progeny derived from resistant sources of Prunus davidiana, P. persica var. densa, and cultivated peach (P. persica), along with their parental lines and developed aphid-resistant ornamental peach cultivars, we monitored green peach aphid (M. persicae) infestations from March to May, with weekly surveys. For each plant in the surveyed population, tender leaves were sampled, and genomic DNA was extracted via the Cetyltrimethylammonium Bromide (CTAB) method. Four molecular markers linked to aphid resistance (InDel24, InDel23, P62, and QMR) were selected for PCR amplification using the extracted DNA as a template. The amplification products were separated by polyacrylamide gel electrophoresis, visualized, and analyzed. The universality and accuracy of these markers were evaluated by integrating phenotypic data from peak aphid infestation periods. Validated markers were then applied to aphid-resistant ornamental peach cultivars. Additionally, from June to July, fruit maturity was assessed weekly. Six fruits at 80% maturity, uniformly distributed on the outer canopy, were sampled per tree to measure single-fruit weight and soluble solid content (SSC). These data were combined to screen for elite aphid-resistant individuals with desirable fruit quality traits. [Results] (1) The InDel24 molecular marker originated from the Zhou Xing Shan Tao (ZXST), demonstrated strong universality in hybrid populations derived from ZXST with aphid resistance. In progeny populations from the cross between ZXST and Nan Yi Qu Xi 29-13, the marker achieved accuracy rates of 100%, 99.21%, 100%, and 100% in populations 1, 2, 3 and 4, respectively, confirming its utility for genotyping these hybrids. However, this marker showed no applicability in other resistant populations. The P62 marker exhibited 99.21% accuracy in hybrid populations with P. persica var. densa ancestry (population 4), but proved ineffective in other genetic backgrounds. Notably, neither InDel24 nor P62 could amplify polymorphic fragments in resistant P. persica progeny (population 5), rendering them unsuitable for genotyping aphid-resistant genotypes in this population. Although derived from P. persica resistance, the InDel23 marker similarly failed to differentiate genotypes in population 5. In contrast, the QMR marker produced distinct bands enabling genotype discrimination, albeit with a modest accuracy rate of 62.61%. It is noteworthy that while the P62 marker successfully amplified homologous genes in both ZXST and Nan Yi Qu Xi 29-13, validation experiments confirmed its inability to discriminate genotypes in their hybrid progeny. (2) In the F3 progeny population derived from ZXST hybrids, fruit maturation was concentrated between late June and mid-July. The fruit size predominantly fell into the small-fruit category (50 g<average single fruit weight ≤ 100 g), with four individuals reaching the medium-fruit standard (100 g<average single fruit weight ≤ 150 g). All evaluated individuals exhibited high soluble solid content (SSC) levels (12% ≤ SSC<14%), with nine plants achieving the extremely high standard (SSC ≥ 14%). Based on these comprehensive evaluations, we identified 12 aphid-resistant individuals with superior agronomic traits that were suitable for direct selection in breeding programs. (3) Using the above molecular markers, the genotypes of the bred peach aphid-resistant ornamental peach varieties were identified and their resistance sources were traced. It was found that the resistance band of Bao Chun could only be detected in the peach aphid-resistant marker from ZXST, and the genotype was AAbb; the resistance bands of Zhong Bi Zhi Chun Shou Xing, Zhong Bi Hong Long Zhu and Zhong Bi Fen Chong Long Zhu could only be detected in the peach aphid- resistant marker from Shou Xing Tao, and the genotypes were all aaBB. Notably, only three cultivars Yuan Chun, Yin Chun, and Hua Chun Shou Xing possessed dual- origin resistance. We hypothesized that in single-resistant cultivars, heterozygous parental genotypes during hybridization led to segregation and subsequent loss of resistance alleles from one origin in the progeny. [Conclusion] The populations and molecular markers employed in this study encompassed three distinct sources of green peach aphid resistance. Among these, InDel24 and P62 demonstrated high accuracy rates for aphid-resistant plants and their hybrid progenies derived from P. davidiana and P. persica var. densa, respectively, indicating significant potential for breeding applications. However, in aphid-resistant progeny originating from P. persica sources, none of the three markers (InDel24, InDel23, or P62) could effectively discriminate resistant genotypes, with the exception of QMR. Notably, the QMR marker exhibited only moderate accuracy (62.61%), suggesting that further research is required to develop more reliable molecular markers for identifying aphid resistance in cultivated peach germplasm.